FROTA PRÓPRIA OU TERCEIRIZADA: UMA ANÁLISE COMPARATIVA DE CUSTOS APLICADA NA UNIVERSIDADE FEDERAL DO ESPÍRITO SANTO NO CAMPUS SÃO MATEUS - Braz, Erivelton Toreta (2021)
Introduction: The contingency of resources carried out by the Federal Government in 2019 affected several Federal Universities, including the Federal University of Espírito Santo (UFES), so several relevant services were impacted, including the institutional road transport services for cargo and passengers. The problem that arises from this context is: starting from a comparative analysis of costs between total outsourcing of services, use of own fleet or hybrid model, what is the best alternative for providing cargo and passenger transport services in the Board of North Sector Infrastructure, São Mateus campus? The main objective was to carry out a comparative cost analysis with a view to finding the best alternative for providing services in the researched institution. In theoretical terms, the research is based on theories about logistics and supply chain, cost management, Taxigov and sector norms and legislation. As for the methods and procedures, documental and bibliographic research was used, also configuring itself as a descriptive research. Data were obtained from Official Vehicle Control Maps provided by the North Sector Infrastructure Directorate and information surveys from organizational portals in the public domain such as the "Price Panel", "Federal Government Purchasing Portal" and "Transparency Portal" ”. With the implementation of the methodology for quantifying total costs (fixed and variable) per kilometer traveled, as well as the survey of the cost per kilometer traveled of hiring outsourced companies carried out by public agencies in Espírito Santo or neighboring regions, it was possible to draw comparisons between these alternatives using the Balance Point (PE) analysis. The results show that in 2019, the fleet consisted of 13 vehicles classified as: four cars, one truck, two minibuses, two pick-ups and four vans with an average age of eight years; that fluctuating demand is linked to the institution's academic calendar; that “drivers' salaries” are highlighted in the composition of fixed costs and that the maintenance cost follows the same trajectory when referring to the variable costs of the own fleet. Considering then the values found, the planning of future needs, the disposal of the surplus fleet and reanalysis of the break-even point, it can be concluded that for the categories "automobile", "minibus", "pick-up" and "vans" , the own fleet must be used up to the limit defined in the planning, seeking the least possible idleness of resources, and when the demand exceeds the daily service capacity (vehicles and drivers) or for displacements with a radius greater than 250 km, it suggests the use the Taxigov alternative for the “automobile” category and contracting outsourced companies for the “minibus”, “pick-up” and “vans” categories. With regard to the “truck” category, the sale of all vehicles in this category and the hiring of companies to provide outsourced services only is suggested. From the results, as a technological product, the “Conclusive Technical Report: Plan for the implementation of a hybrid strategy with the use of its own and outsourced fleet at the Federal University of Espírito Santo on the São Mateus campus.”